Prevalence and impact of ischemic risk on long-term bleeding and ischemic event for high bleeding risk patients. (25th November 2020) - Shima, Y; Miura, K; Tada, T; Tanaka, H; Fuku, Y; Kadota, K
Abstract: Background: Impact of ischemic risk (IR) on long term outcomes in patients at high bleeding risk (HBR) after everolimus-eluting stent (EES) implantation remains unclear. Purpose: We aimed to evaluate long term bleeding and ischemic events in patient with HBR or IR after EES implantation. Methods: The study population comprised 1219 patients treated with EES without in-hospital events between 2010 and 2011. The follow-up period was 2996±433 days. HBR was defined as Academic research consortium. IR defined as high-risk features of stent-driven recurrent ischemic events in Europe society of cardiology guidelines in 2019: prior stent thrombosis on adequate antiplatelet therapy, diffuse multivessel disease especially in diabetic patients, creatinine clearance <60 ml/min, at least three stents implanted, bifurcation two stents implanted, total stent length >60 mm, and treatment of a chronic total occlusion. Major bleeding (MB) was defined as defined as the occurrence of a Bleeding Academic Research Consortium (BARC) type 3 or 5 bleeding event. Primary ischemic events included myocardial infarction, definite stent thrombosis, and cardiac death. The Kaplan-Meier method was used for time-to-event analyses. Results: Of the 1219 patients, 317 (26.0%) patients had no risk, 114 (9.4%) patients had only HBR, 288 (23.6%) patients had only IR, and 500 (41.0%) patients had both risks. The 81.4% of HBR patients had IR. The figure of Kaplan-Meier showed MB and CE for 7–8 years. Both risk groups had higher bleeding risk and Ischemic events (log rank p=0.0039, 0.0001). Conclusion: HBR patients with EES had a high incidence of IR. Patients who had both HBR and IR are especially at risk for both ischemic events and bleeding compared to those who had no or only one risk. Funding Acknowledgement: Type of funding source: None